2011
DOI: 10.1111/j.1742-7843.2011.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Rotundifolone-Induced Relaxation is Mediated by BKCa Channel Activation and Cav Channel Inactivation

Abstract: Rotundifolone is the major constituent of the essential oil of Mentha x villosa Hudson. In preliminary studies, rotundifolone induced significant hypotensive, bradycardic and vasorelaxant effects in rats. Thus, to gain more insight into the pharmacology of rotundifolone, the aim of this study was to characterize the molecular mechanism of action involved in relaxation produced by rotundifolone. The relaxant effect was investigated in rat superior mesenteric arteries by using isometric tension measurements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
(45 reference statements)
1
29
0
1
Order By: Relevance
“…Regarding ROT some effects reported in the literature, analgesic (Almeida et al, 1996), relaxant (Sousa et al, 2007), hypotensive and bradycardic (Guedes et al, 2002), antinociceptive (Sousa et al, 2007(Sousa et al, , 2009, antimicrobial (Arruda et al, 2006) and spasmolytic (Sousa et al, 2008). Studies have also demonstrated a possible mechanism of action involved in the relaxing effect exhibited by ROT (Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding ROT some effects reported in the literature, analgesic (Almeida et al, 1996), relaxant (Sousa et al, 2007), hypotensive and bradycardic (Guedes et al, 2002), antinociceptive (Sousa et al, 2007(Sousa et al, , 2009, antimicrobial (Arruda et al, 2006) and spasmolytic (Sousa et al, 2008). Studies have also demonstrated a possible mechanism of action involved in the relaxing effect exhibited by ROT (Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For this we used Tyrode's solution modified with 20 mM KCl, a concentration sufficient to partially prevent efflux of K + and attenuate vasorelaxation mediated by the opening of K + channels [16, 17]. Additionally, we also experimented using TEA, a blocker of K + channels, at different concentrations (1, 3, and 5 mM) [2729]. In all these situations, the effect of JSJ was significantly attenuated, and, for the differing TEA concentrations, the effect was concentration-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were euthanized, and superior mesenteric artery was removed, cleaned from connective tissue and fat as described by Silva and colleagues [10]. Whenever appropriate, the endothelium was removed by gently rubbing the intimal surface of the vessels.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the involvement of K + channels, in the first set of experiments, vasorelaxation with VPR was performed in vessels with denuded endothelium that were precontracted with Phe in Tyrode's solution with elevated K + (20 mM equimolar replacement of NaCl with KCl) to attenuate K + efflux [10]. Additionally, in the second group of experiments, endothelium-denuded rings were incubated for 30 min with putative K + channel blockers before the second application of Phe (1  μ M), and the inhibition was calculated by comparing the response elicited by VPR, before and after the addition of the inhibitors.…”
Section: Methodsmentioning
confidence: 99%